1999
DOI: 10.1016/s0014-5793(98)01625-1
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of T7 RNA polymerase active site with novel reagents – oligonucleotides with reactive dialdehyde groups

Abstract: Oligonucleotides of a novel type containing 2P-O-L Lribofuranosyl-cytidine were synthesized and further oxidized to yield T7 consensus promoters with dialdehyde groups. Both types of oligonucleotides were tested as templates, inhibitors, and affinity reagents for T7 RNA polymerase and its mutants. All oligonucleotides tested retained high affinity towards the enzyme. Wild-type T7 RNA polymerase and most of the mutants did not react irreversibly with oxidized oligonucleotides. Affinity labeling was observed onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 17 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…ODNs containing 3'aldehyde groups were prepared on modified support. 15A) [63]. The ODN-aldehyde was conjugated to alkaline phosphatase to obtain the ODN-enzyme conjugate that showed unaltered hybridisation properties.…”
Section: Conjugation Via Reductive Amination Hydrazone or Oxime Linkagementioning
confidence: 99%
“…ODNs containing 3'aldehyde groups were prepared on modified support. 15A) [63]. The ODN-aldehyde was conjugated to alkaline phosphatase to obtain the ODN-enzyme conjugate that showed unaltered hybridisation properties.…”
Section: Conjugation Via Reductive Amination Hydrazone or Oxime Linkagementioning
confidence: 99%
“…It was shown that modified ON formed stable complexes with complementary DNA ( Tm= 0-3°C) [93]. DNA duplexes bearing extra dialdehyde groups were used for affinity modification of T7 RNA polymerase [94] and restriction-modification enzymes EcoRII and MvaI [93,95]. The data obtained revealed the localization of DNA-binding sites of these enzymes.…”
Section: Oligonucleotides Containing Disac-charide Nucleosidesmentioning
confidence: 99%
“…To study T7 RNA polymerase and its mutants, modified ON duplexes, containing the T7 RNA polymerase promoter and five transcript base pairs were used [94]. It was shown that duplexes bearing 2 -O--D-ribofuranosylcytidine or its oxidized derivative were competitive inhibitors of T7 RNA polymerase, the values of binding constants being 2-3.5 times lower than in the case of the reference unmodified duplex.…”
Section: Oligonucleotides Containing Disac-charide Nucleosidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Oligonucleotides 148 containing a dialdehyde group in the 2 H -position were used for the study of protein-NA interactions with restriction endonuclease EcoRII, DNA-methyltransferases EcoRII, 371 MvaI (see Refs 372 ± 374) and T7 RNA polymerase. 373,375 The use of modified oligonucleotides permits one to inhibit the enzyme activity without any effect on the ability of enzymes to bind the NA substrate. The interaction of oligonucleotides 148 with enzymes occurs in a selective manner and involves the e-amino groups of lysine.…”
Section: B Studies Of Dna7protein Interactionsmentioning
confidence: 99%